2013
DOI: 10.1002/ijc.28532
|View full text |Cite
|
Sign up to set email alerts
|

Impact of technology on cytology outcome in cervical cancer screening of young and older women

Abstract: Little is known about age-dependent variation in outcomes of cervical cytology with modern technologies. This populationbased study evaluated age-dependent changes after routine implementation of ThinPrep and SurePath technology in two independent laboratories, and controlled for time trends in a third laboratory using manually read conventional cytology continually. Data were collected from the Danish National Health Care Registers. For each laboratory, we compared proportions of abnormal cytology defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 27 publications
0
28
0
1
Order By: Relevance
“…During the period, several Danish pathology departments changed from conventional, manually read Papanicolaou (Pap) smears to automation-assisted reading of liquid-based cytology, and possibly this transition may have influenced the incidence. Two Danish studies of the impact of cervical screening technology at different hospitals in the greater Copenhagen area showed notable differences in the results obtained with the two techniques [46,47] although a metaanalysis did not find that liquid-based cytology was more sensitive or more specific for detecting cervical lesions [48]. In a study of almost 400,000 cervical samples, Barken et al [46] found that a change from conventionally read Pap smears to automation-assisted reading of liquid-based cytology increased the proportion of samples with atypical squamous cells of undetermined significance (ASCUS) or worse from 3.8 to 6.0 % during 1998-2007.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…During the period, several Danish pathology departments changed from conventional, manually read Papanicolaou (Pap) smears to automation-assisted reading of liquid-based cytology, and possibly this transition may have influenced the incidence. Two Danish studies of the impact of cervical screening technology at different hospitals in the greater Copenhagen area showed notable differences in the results obtained with the two techniques [46,47] although a metaanalysis did not find that liquid-based cytology was more sensitive or more specific for detecting cervical lesions [48]. In a study of almost 400,000 cervical samples, Barken et al [46] found that a change from conventionally read Pap smears to automation-assisted reading of liquid-based cytology increased the proportion of samples with atypical squamous cells of undetermined significance (ASCUS) or worse from 3.8 to 6.0 % during 1998-2007.…”
Section: Discussionmentioning
confidence: 97%
“…In a study of almost 400,000 cervical samples, Barken et al [46] found that a change from conventionally read Pap smears to automation-assisted reading of liquid-based cytology increased the proportion of samples with atypical squamous cells of undetermined significance (ASCUS) or worse from 3.8 to 6.0 % during 1998-2007. Rask et al [47] found that use of imaging-assisted reading increased the proportion of samples with ASCUS or worse by about 30 % in all age groups. Although these two studies investigated cytological samples, while we investigated incidence trends of histologically verified diagnoses only, it is reasonable to assume that detection of more abnormal cytological diagnoses would result in more biopsies being performed and, hence, an increase in diagnoses of CIN3 and AIS.…”
Section: Discussionmentioning
confidence: 98%
“…proxy for the laboratories involved) and the type of primary cytology test used seems to confirm this, and could partly explain the increase in the number of cytological smears classified as BMD or >BMD, although the implementation of imaging-assisted reading could also have contributed. 12 Increased attendance of previously unscreened women may also have contributed to the CIN increase, although coverage rates of the screening 14 Increased CIN DRs may have been a compensation for the observed previous decrease in CIN detection. This decrease was probably the effect of a period with increased screening intensity from 1996 to 1998, when the age range eligible for screening was extended from 35-53 years to 30-60 years and several extra birth cohort were invited.…”
Section: Outmentioning
confidence: 99%
“…age, screening region, and SES) and differences in types of cytology tests used over time. As the effect of the type of primary cytology test used could differ between age groups 12 and laboratories, we included two-way interaction terms between the type of primary cytology test and age, and between the type of primary cytology test and screening region (ie. as proxy for the laboratories involved).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In 2016, where the majority of the 1993 cohort was screened, all of Denmark had changed to liquid-based cytology mostly SurePath. For selected laboratories, we have found previously that the shift to SurePath was associated with an increase in the ASCUS detection rate in young women [5]. In Denmark, women below the age of 30 years with ASCUS are referred for repeated screening in 6 months, and only referred for a gynecologist if their cytology continues to be abnormal.…”
Section: Hpv-vaccination In Denmark: Impact On Cervical Cancer Riskmentioning
confidence: 99%